(untitled) (Slavic Studies, 2025)
Drawing on key analytical concepts from feminist narratology, particularly those introduced by Susan Lanser, as well as Nancy Armstrong’s critique of the realist novel, this paper examines the interplay between narrative structure and the feminist aspirations of Eliza Orzeszkowa’s 19th century novel Marta. Situating the novel within the broader socio-political context of 19th century Poland, the study explores how Marta both critiques and reflects the patriarchal and economic conditions shaping women’s lives during this period. Through close reading as its primary method, the analysis demonstrates how, in the pursuit of its thematic objectives, the text engages with, subverts – or is constrained by – the limitations inherent in the realist narrative form.